Pengaruh Islamic Branding Dan Personal Selling Terhadap Buying Decision Pada Produk HNI-HPAI - Melati, Sintia; Siregar, Onan Marakali (Jurnal Ilmiah Wahana Pendidikan, 2025)
One of the companies engaged in halal health products is HNI-HPAI, however, this company still needs to improve Islamic branding and personal selling to reach consumers in Medan City so that consumers make buying decisions. This study aims to determine the effect of Islamic branding, and personal selling, on buying decisions on HNI HPAI products in Medan City. This form of research is quantitative research with an associative approach. The population in this study were consumers of HNI-HPAI products in Medan City, with a sample of 96 respondents, with sampling techniques using purposive sampling. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and determination coefficient tests. The results of this study indicate that Islamic branding and personal selling have a positive and significant effect on the buying decision variable, and have an effect of 77.3%, while the remaining 22.7% is influenced by other factors outside this research model.